1995
DOI: 10.1021/j100011a003
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopic Detection of CO Formed at Step and Terrace Sites on a Corrugated Electrode Surface Plane during Methanol Oxidation

Abstract: A platinum single crystal electrode with ordered step and terrace structures was used to probe site-dependent aspects of methanol surface chemistry. Infrared spectral features of the adsorbed CO reaction intermediate were measured in parallel experiments with Pt(335) (Pt(s)-[4( 11 1) x (loo)]) and Pt( 11 1) electrodes.Experiments confirm that methanolic CO formation is inhibited at Pt( 11 1) at potentials in the hydrogen adsorption region, and they reveal that methanol dissociative chemisorption proceeds to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 8 publications
7
42
0
1
Order By: Relevance
“…From the previous studies of methanol oxidation on various Pt stepped surfaces, the results seem to be quite controversial when the role of the presence of different steps on (1 1 1) terraces and its effect is discussed [15][16][17]. So the point of our work is to make clear the influence of different steps and the step density on Pt(1 1 1) and (1 0 0) surfaces for the methanol oxidation reaction.…”
Section: Introductionmentioning
confidence: 94%
“…From the previous studies of methanol oxidation on various Pt stepped surfaces, the results seem to be quite controversial when the role of the presence of different steps on (1 1 1) terraces and its effect is discussed [15][16][17]. So the point of our work is to make clear the influence of different steps and the step density on Pt(1 1 1) and (1 0 0) surfaces for the methanol oxidation reaction.…”
Section: Introductionmentioning
confidence: 94%
“…Wang et al20 compared the potentiodynamic oxidation of methanol at smooth polycrystalline platinum, Pt(111), and Pt(332) electrodes and found that methanol oxidation is enhanced with increasing step density without an appreciable increase of the CO 2 current efficiency; hence, they concluded that the defect sites enhance both parallel pathways of methanol oxidation. Shin and Korzeniewski21 suggested that an increase of the step density catalyzes methanol decomposition and the methanolic CO formation is inhibited on Pt(111) at the potential of the hydrogen adsorption. Tripkovic and Popovic22 reported that the initial surface activity for methanol oxidation on stepped electrodes decreases with increasing step density whereas Housmans et al7 found that the overall oxidation rate of methanol increases with increasing step density.…”
Section: Introductionmentioning
confidence: 99%
“…Because of a higher density of step and kink sites, a surface plane with a high Miller index generally has a greater catalytic activity than one with a low Miller index [81,82] . A challenge in optimizing the geometry of NPs for catalysis is that particles with high -index facets are diffi cult to synthesize.…”
Section: Particle Shape Dependencementioning
confidence: 99%